HelloTalk Users’ Interpretation of Language Cues: A Mixed-Method Case Study - N. Aini Hasyim Munthe Borneo; Mutiara Salsabila Harahap; Deasy Yunita Siregar (EXCELLENCE: Journal of English and English Education, 2025)
As language learning shifts to digital platforms, the absence of non-verbal signals creates linguistic ambiguity that risks intercultural misunderstanding. This study examines how HelloTalk users interpret language registers and apply Communication Accommodation Theory (CAT) within a mixed-purpose digital ecosystem. Using a Concurrent Mixed-Method approach, data were collected from ten B2+ users via Likert scales and thematic analysis. Findings reveal strong register awareness for serious topics (mean=4.30), yet significant ambiguity exists when interpreting formal language in casual chat (s=1.29), hindering pragmatic interlanguage development. Qualitatively, the primary barrier to decoding cues is not linguistic structure, but phonetic factors such as non-standard accents and rapid speech. The study concludes that effective accommodation is constrained by these phonetic hurdles and conflicting digital cues. These results offer critical insights for Mobile Assisted Language Learning (MALL) development, highlighting the need for interfaces to better mediate paralinguistic elements in peer-to-peer digital interactions.